Cognition and Vascular Risk Factors: An Epidemiological Study - Augusto Vicario; Mildren Del Sueldo; Ruth A. Fernández; Julio Enders; Judith Zilberman; Gustavo H. Cerezo (International Journal of Hypertension)
We conducted an epidemiological approach to identify the negative impact of the vascular risk factors (such as hypertension, diabetes and hypercholesterolemia) over cognition. The interesting aspect of this study was that the survey was conducted in all age groups through a voluntary call (n=1365; ≥18 years old, both sexes; age 49 ± 15 y, female 75.7%). Thus, we demonstrated that the use of a Minimum Cognitive Examination (MCE), a brief, simple, and easy managed neuropsychological evaluation, detected a greater number of people with cognitive decline surpassing to the Minimal Mental Statement Examination alone (14.5% of the participants showed MMSE ≤24, 34,6% showed dys-executive function, and 45,8% memory impairment. Out of the 4 studied RF, the only one that was not related to cognitive impairment was dyslipemia. Finally, we noted the importance of cognitive state early detection in all age groups, even in the youngest group. Acting in the middle of the life stages, we can prevent or delay the onset of a disease in adults, nowadays incurable: dementia.